Low Tortuosity and Reinforced Concrete Type Ultra‐Thick Electrode for Practical Lithium–Sulfur Batteries. (3rd December 2021) - Han, Zhilong; Li, Shuping; Xiong, Ruoyu; Jiang, Zhipeng; Sun, Mengjun; Hu, Wei; Peng, Linfeng; He, Renjie; Zhou, Huamin; Yu, Chuang; Cheng, Shijie; Xie, Jia
Abstract: High‐energy density and ultra‐long cycling lifespan are of great significance in pursuit of practical lithium–sulfur (Li‐S) batteries, in which the construction of ultrathick, high‐areal‐capacity, and stable‐cycling sulfur cathodes remains challenging. Here, a unique layered reinforced concrete structure (LRCS) is reported by integrating an ice‐template method with incorporating carbon fibers in the thick electrodes for Li‐S batteries. The LRCS enables aligned through‐channel structure and intertwined conductive network, which lead to both fast kinetics of ions/electrons transport and strengthened electrode integrity to tolerate the volume change during cycling and the dimensional deformation under a high compaction density. Benefiting from the unique structure, the ultra‐thick Se0.05 S0.95  @ pPAN cathode (20.2 mg cm −2 ) delivers a high capacity of 10 mAh cm −2 and excellent capacity retention of 80.8% over 140 cycles at a low electrolyte‐to‐sulfur ratio of 2 and a negative‐to‐positive capacity ratio of 2.7, corresponding to a calculated energy density of 390 Wh kg −1 . This investigation not only provides guidance for the design of thick sulfur electrodes but also paves the way for the development of practical Li‐S batteries. Abstract : The layered reinforced concrete structure enables sulfur cathode with aligned through‐channel and intertwined conductive network, leading to fast kinetics and strengthened integrity during cycling. Benefiting from the unique structure, the ultra‐thick sulfur cathode delivers a high capacity of 10 mAh cm −2 and excellent cycling life (80.8%) over 140 cycles under lean electrolyte (E/S=2) and limited lithium (N/P=2.7).